Legal Issues Facing the Termination of Employment Contracts in the Digital Work Environment: A Descriptive and Analytical Study - Shahad Musfir Saeed Al-Qahtani; Amal Shalabi Khadragey (International Journal of Law Research and Studies, 2026)
This study sheds light on the legal challenges confronting the termination of employment contracts within the digital environment, amid the profound digital transformation and the emergence of remote work patterns. The core problem lies in the difficulties encountered when applying the traditional substantive rules outlined in Saudi labor law to virtual work settings, particularly regarding the termination of the contractual relationship between the worker and the employer, and the challenges in proving worker negligence. The study aims to elucidate the concept of digital contract termination and outline the position of Saudi law concerning such contracts. Employing the descriptive and analytical methodologies, the study reviews and analyzes relevant statutory provisions. It is structured into two main sections: the first addresses the nature of digital contract termination and the legal validity of electronic notification methods, while highlighting the effective role of governmental platforms—such as the Qiwa platform—in documenting procedures and mitigating disputes. The second section examines practical challenges in termination, specifically the difficulty in distinguishing intentional negligence from technical malfunctions. The study concludes that applying traditional provisions of Saudi labor law to remote employment contracts generates challenges necessitating regulatory intervention. Despite the successes of digital platforms, it recommends that Saudi legislative authorities address substantive gaps by establishing precise standards across various aspects of the digital employment contract, thereby ensuring equitable balance, workplace stability, and the protection of both parties’ rights.